Analisis Budaya Kerja, Kepemimpinan, dan Pendidikan Pengembangan Spesialisasi terhadap OCB dengan Motivasi Kerja sebagai Variabel Intervening - Andhi Setyawan; Kusuma Chandra Kirana; Ambar Lukitaningsih (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study plans to decide the impact of work culture, leadership, and specialization advancement training on OCB through inspiration as a mediating variable. The exploration populace is all government employees in the Public Police at the Individual Staff Work Unit and the General Secretariat in the Yogyakarta Extraordinary Area Provincial Police, adding up to 46 respondents with an example of 43 respondents. Gathering information utilizing a poll with the Krejcie-Morgan strategy and arbitrary examining method. This examination strategy utilizes a quantitative methodology with the SmartPLS3.2.8 application. The consequences of the review demonstrate that work culture, authority and specialization advancement schooling affect work inspiration, work culture, administration and specialization improvement instruction significantly affect OCB straightforwardly or through inspiration as a mediating variable Keywords: work culture, leadership, specialization development education, OCB, work motivation.